Pengaruh Good Corporate Governance Terhadap Kinerja Perusahaan Manufaktur (Studi Empiris Laporan Keuangan Perusahaan Manufaktur yang Terdaftar di BEI, periode 2010-2012) - Tabah Amirul Masjid, Muhammad; , Drs. Yuli Tri Cahyono , M.M., Akt., CA (2015)
The purpose of this study is to empirically examine the effect of good corporate governance to corporate performance (Tobin's Q) in the manufacture company. Corporate governance components in this study is audit committee, board of director, quality of public accounting firm, and independent board. Population in this study is manufacture company which listed on BEI in period 2010-2012, with the sampling method is purposive sampling method. This research was conducted by using documentation method which used data from annual financial statements listed in Indonesia Stock Exchange (BEI) and the data from Indonesian Capital Market Directory (ICMD). The method of data analysis is used a multiple regression analysis. The sample used in this study amounted to 234 manufacture company listed on the Indonesia Stock Exchange in the period 2010-2012. The results of this research demonstrate that board of director variable and quality KAP have a significant effect on firm performance, while audit committee variable and independent board has no significant effect on firm performance (Tobin's Q).